Combined experimental and theoretical study of visible light active P doped TiO2 photocatalyst. (19th June 2017) - Gul, Sahar Ramin; Khan, Matiullah; Wu, Bo; Yi, Zeng
Abstract: Using the hydrothermal method, a P-doped TiO2 nano-catalyst is prepared for widening the application spectrum of TiO2 . The synthesized samples are investigated using XRD, TEM, and UV–visible absorption spectra. A P-doped TiO2 system is simulated and calculations for geometrical structure, electronic and optical properties are performed based on density functional theory. Comparison of the electronic band structure of anatase TiO2 before and after doping verified that doping tuned the band structure. XRD patterns revealed that pure anatase phase is the only phase in case of pure and doped samples. TEM observations reveal spherical morphology. The P doped TiO2 experimentally as well as theoretically responded to visible light confirming the band structure findings. Photocatalytic activity of the doped samples drastically improved compared to bare TiO2 .